Technological Tools for the Teaching and Learning of Statistics - Tolentino, Mark Anthony C (Archīum Ateneo, 2023)
Statistics and its applications form an integral part of STEM education. In the literature, it is shown that technology is valuable in supporting the teaching and learning of statistics. This paper discusses some technological tools that have been developed to support statistics education in the grade school, junior high school, and senior high school levels. It describes the design and pedagogical basis of these tools, and how these may be integrated in the classroom.